2009
DOI: 10.1677/jme-09-0009
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumours: all silent on the epigenetics front

Abstract: Investigation of the epigenome of sporadic pituitary tumours is providing a more detailed understanding of aberrations that characterise this tumour type. Early studies, in this and other tumour types adopted candidate-gene approaches to characterise CpG island methylation as a mechanism responsible for or associated with gene silencing. However, more recently, investigators have adopted approaches that do not require a priori knowledge of the gene and transcript, as example differential display techniques, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 44 publications
0
35
0
3
Order By: Relevance
“…It has been demonstrated that, in pituitary tumors, promoter methylation is a frequent event. 55,56 Bello et al 57 reported that MGMT was methylated at significant rates in both functional and nonfunctional adenomas. This epigenetic alteration may disrupt the key cellular functions of MGMT and contribute to pituitary adenoma development.…”
Section: Mgmt Immunoexpressionmentioning
confidence: 99%
“…It has been demonstrated that, in pituitary tumors, promoter methylation is a frequent event. 55,56 Bello et al 57 reported that MGMT was methylated at significant rates in both functional and nonfunctional adenomas. This epigenetic alteration may disrupt the key cellular functions of MGMT and contribute to pituitary adenoma development.…”
Section: Mgmt Immunoexpressionmentioning
confidence: 99%
“…[2] In common with most other tumour types the genesis of pituitary tumours is consequent to the combined contribution of genetic and epigenetic aberration, targeting the genome and epigenome respectively. [3,4,2,5] The relative contributions of these aberrations, their order of appearance, and the way in which their effects are manifest are largely unknown, however, specific aberration, be they genetic or epigenetic, are either common or particular to an adenoma subtype(s). [6,5,7] Moreover, the demarcation between genetic and epigenetic aberrations are perhaps less precise than initial findings suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies provide a mechanism underlying a common, problematic intracranial neoplasm affecting children, and the animal model they developed accurately predicted markers in human craniopharyngiomas. This work represents an important step in understanding the etiology of pituitary adenomas and sets the stage for exploring the role of epigenetics and tumor suppressors in normal and abnormal pituitary development (27).…”
Section: Resultsmentioning
confidence: 99%
“…Gaston-Massuet et al clearly show that mutants do not express Pou1f1 or the target genes growth hormone and thyroid stimulating hormone at the appropriate time, and Pou1f1 expression is blocked in mutant pituispheres (3). Further studies will reveal the complete mechanism of Pou1f1 regulation, including the role of corepressors, epigenetic regulation, and microRNAs (25)(26)(27).…”
Section: Study Raises Several Questions About Regulation Of Pituitarymentioning
confidence: 97%